Análise técnica e econômica entre o veículo elétrico Nissan Leaf e o veículo a combustão interna Nissan Versa. - Pangoni, Fabricio; Pereira Silva, Ramon Eduardo (Latin American Journal of Energy Research, 2023)
This article presents a technical and economic comparative proposal between the use of the internal combustion vehicle (VCI) Nissan Versa with the electric vehicle (EV) Nissan Leaf for use by a family living in the city of Campo Grande – MS, powered or not. by a grid-connected photovoltaic system (SFVCR) in 5 scenarios. For the technical analysis, the sizing of the SFVCR, sizing of the circuit for the charging station and vehicle consumption were considered. For the economic analysis, a 96-month projection was used, costs with the SFVCR, infrastructure for installing the charging station, acquisition, maintenance, licensing, IPVA and fuel costs. The apportionment was made for the residence and the vehicle. To study the financial expense used, Payback, Net Present Value (NPV) and Internal Rate of Return (IRR) are used. As a result, the analysis concluded that, for the 15 situations studied, the VCI is more financially viable, followed by the VE using the SFVCR and finally the use of the VE